RANCANG BANGUN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA PT BILLINDO UTAMA - Liem, calven; Amrizal, Amrizal (LPPM Universitas Putera Batam, 2021)
PT Billindo Utama is a company engaged in the sale of general supplier, marine, hardware, tools & equipments and was founded in 2010, located in tanjung uncang, riau island, batam. The problem being faced by Billindo Utama is the order system is still oflline so that it doesn’t make it easier for customer to make purchase, this COVID19 virus pandemic must follow health protocols and can reduce visiting customer, and there is no customer database systematically recapitulated in a systemized manner which can pose a risk of losing customer data. If Billindo Utama markets its products throught web e-commerce then the problems faced by Billindo Utama at this time will be solved. Based on the problems being faced by Billindo Utama the researchers will conduct research with aim of to find out how to design and implement a web-based sales information system at Billindo Utama. The method used in the research process is the SDLC waterfall model which consists of system analysis, system design, coding, and testing. The results of research on Billindo Utama is this e-commerce web can facilitate transactions, marketing, and all product information will be conveyed and it’s hoped that next system developer can add some features. Keywords: System, Information, E-Commerce, COVID19, Web